Exploring the contextualization of workplace spirituality in South Korean startups - Ahreum Lim; Nicolaides Aliki; Chan Lee (Adult Education Research Conference, 2020)
This study explores how spirituality in workplaces is contextualized in South Korean startups. With the unprecedented development of technology, new small-sized ventures, so-called startups have emerged as the major drivers in today’s global market (Schwab, 2017). The disruptive changes that startup creates in the market imply the growing needs of both organizations and individuals to be more adaptive to the given changes. Backing up these trends, an increasing amount of new consumers’ needs is fulfilled through innovative breakthrough, possibly only temporarily, at the expense of tremendous stress that individual employees at startups suffer from. Nonetheless, to survive through the volatile market, secure the competitive edge of the fast-paced industry as well as to create an inclusive work environment, numerous startups emphasized entrepreneurial orientation as well as team spirit. Here, entrepreneurial orientation means the ideation and implementation of new ideas as well as the exploration of new business opportunities. Additionally, team spirit refers to team members' attached feelings to commit themselves to their team's shared goal. The emphasis on the spiritual dimension of entrepreneurship and teamwork aligns with the "spiritual movement”(Ashmos and Duchon, 2000). Based on the paradigm shift in organization science, which leads to the empowerment of individuals by prioritizing employee's work-life balance, spirituality in workplaces has gained much attention in the early 2000s. This movement aims to make the workplace more inclusive so that spirituality enhances individual employees' well-being, highlights their self-existential meaning in workplaces, and deepens the understanding of interconnectivity with others (Karakas, 2010; Houghton, Neck and Krishnakumar, 2016). Despite the debate over defining spirituality, a plethora of empirical studies have substantiated the positive effect of spirituality at workplaces, especially regarding the link between spirituality and performance/productivity (Giacalone and Jurkiewicz, 2003; Duchon and Plowman, 2005; Rego, Cunha, Souto, 2007; Petchsawang and Duchon, 2012). As the efforts that South Korean startups have exhibited to link this ‘spirit’ discourse to their productivity aligns with the aforementioned spiritual movement in workplaces, this study is designed to seek an answer to the fundamental question around this matter; does the emphasis on ‘spirit’ positively influence the perceived productivity in South Korean Startups? To corroborate this link, this study explores the mediating effect of team spirit in the relationship between entrepreneurial orientation and the team's performance towards the South Korean startups. Based on the analysis of 240 responses from 66 startup teams, this study concludes that team spirit fully mediates the positive association between entrepreneurial orientation and team productivity. The conclusion also suggests the organizational development strategy to build a more inclusive workplace for startup employees.
Keywords: Startups; Team Spirit; Workplace Spirituality; South Korea